Global navigation approach for assistant robot (2016)
Context: This work shows a novel navigation approach based on images for an assistant hybrid robot composed by a humanoid and an omnidirectional platform. Method: This approach introduces a complex space analysis, using Zeros and Poles attraction-repulsion principle. In order to perform the algorithm, an integrated system is developed; this system includes: an external camera to take a global navigation surface view, the assistant robot, and communication devices. Navigation is supported by some digital image processing algorithms and performed using the root location technique. Results: An integrated system of global navigation with external sensors was successfully implemented for the proposed hybrid robot. Conclusions: Some simulation and experimental tests will be discussed in order to validate this proposal and the whole system. Additionally, some suggestions for future research are proposed.